TALENs-mediated gene disruption of myostatin produces a larger phenotype of medaka with an apparently compromised immune system. (January 2016) - Chiang, Yi-An; Kinoshita, Masato; Maekawa, Shun; Kulkarni, Amod; Lo, Chu-Fang; Yoshiura, Yasutoshi; Wang, Han-Ching; Aoki, Takashi
Abstract: Although myostatin, a suppressor of skeletal muscle development and growth, has been well studied in mammals, its function in fish remains unclear. In this study, we used a popular genome editing tool with high efficiency and target specificity (TALENs; transcription activator-like effector nucleases) to mutate the genome sequence of myostatin (MSTN) in medaka ( Oryzias latipes ). After the TALEN pair targeting Ol Myostatin was injected into fertilized medaka eggs, mutant G0 fish carrying different TALENs-induced frameshifts in the Ol MSTN coding sequence were mated together in order to transmit the mutant sequences to the F1 generation. Two F1 mutants with frameshifted myostatin alleles were then mated to produce the F2 generation, and these F2 Ol MSTN null (MSTN −/− ) medaka were evaluated for growth performance. The F2 fish showed significantly increased body length and weight compared to the wild type fish at the juvenile and post-juvenile stages. At the post-juvenile stage, the average body weight of the MSTN −/− medaka was ∼25% greater than the wild type. However, we also found that when the F3 generation were challenged with red spotted grouper nervous necrosis virus (RGNNV), the expression levels of the interferon-stimulated genes were lower than in the wild type, and the virus copy number was maintained at a high level. We therefore conclude that although the MSTN −/− medaka had a larger phenotype, their immune system appeared to be at least partially suppressed or undeveloped. Highlights: TALENs-induced frameshifts in the myostatin (MSTN) coding sequence in medaka. TALENs-mediated MSTN mutations could be transmitted to the next generation. TALENs-mediated MSTN frame-shifted mutation induced the expression of myogenic regulator factors (MRFs). The F2 MSTN −/− medaka showed significantly increased body length and weight compared to the wild type fish. In the TALENs-mediated MSTN −/− fish, there is a failure to trigger an ISG response at least against this virus.